Hydrocele following placement of a ventriculoperitoneal shunt case report - José Sena Calvário; Eliseu Paolioli Neto (Arquivos de Neuro-Psiquiatria)
The authors report the case of a two years old patient with hydrocele alter ventriculoperitoneal shunt procedure.